Juegos y su incidencia en el desarrollo cognitivo de niños de Educación Inicial II - Bravo Rivera, Michael (2025)
The present research aims to determine the impact of games on the cognitive development of children in Early Childhood Education II at the "Alfonso Reyes Falcón" Basic Education School, located in the Simón Bolívar canton, Guayas province, during the year 2024. The population consists of a group of 21 Early Childhood Education II children and their teacher. The study emphasizes the importance of using play as a key pedagogical tool to enhance cognitive skills such as attention, memory, logical reasoning, and creativity in children. A qualitative approach was used, with structured observation techniques and interviews applied to the teacher, allowing for the identification of existing limitations in the implementation of play activities in the classroom. Instruments such as an observation checklist, an-interview guide, and an observation sheet were used. Among the expected results, it is anticipated that games, when planned and executed properly, will significantly foster the development of cognitive skills in children, contributing to a more dynamic and effective learning process. The possible conclusion suggests that the lack of specific teacher training and adequate teaching resources limits the impact of play on children's cognitive development. Therefore, the study proposes the implementation of innovative play methodologies and teacher training as key strategies to optimize learning through play. These actions will contribute not only to the integral development of children but also to the strengthening of educational quality within the institution.